Mycotoxin Contamination of Feeds and Raw Materials in China in Year 2021 - Hao, Wei; Li, Anping; Wang, Jinyong; An, Gang; Guan, Shu (Frontiers in Veterinary Science, 2022)
In this research, we performed a large-scale survey of mycotoxin contamination in several feed commodities and assessed regional differences of mycotoxin occurrence in maize across China in 2021. Concentrations of aflatoxins, zearalenone (ZEN), fumonisins, and trichothecenes type B were analyzed in 2,643 raw material and compound feed samples collected from 8 provinces. Generally, trichothecenes type B, fumonisins, and ZEN were most prevalent and detected in averages of positive concentrations at 1167 µg/kg, 1623 µg/kg and 204 µg/kg, respectively. In the new season maize, samples were also seriously infested with trichothecenes type B, fumonisins, and ZEN, and their averages of positive concentrations are 1302, 2518, and 225 μg/kg, respectively. Wheat was commonly contaminated with trichothecenes type B and ZEN, and the highest concentration levels of trichothecenes type B, fumonisins and ZEN were all detected in the samples from maize by-products. Among the different geographical regions, distinct trends were observed in new season maize. Samples from Shandong province were highly contaminated with trichothecenes type B, fumonisins, and zearalenone, while special attention should be paid to aflatoxins and fumonisins in Anhui and Jiangsu provinces in East China. The present survey also showed that compound feeds and raw materials are commonly contaminated by multiple mycotoxins. Trichothecenes type B and ZEN concentrations were correlated significantly in this survey.